2020
DOI: 10.30574/wjarr.2020.6.2.0129
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects of waste dry cell battery on the haematology and biochemistry of blood, gills and liver of Clarias gariepinus fingerlings

Abstract: Indiscriminate dumping of spent dry cell batteries have continuously polluted aquatic environments usually as surface run-offs with deleterious effects on aquatic fauna including Fish. Toxicity effects of water soluble fractions (WSFs) of waste dry cell battery (WDCB) on blood, gills and liver of Clarias gariepinus fingerlings were investigated under laboratory conditions. Acute (96 hr.) and sub lethal (56 days) bioassays were separately conducted on 120no. C. gariepinus fingerlings stocked ten (10) per tank i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Also,Rahmanet al [64] detected severe necrosis, appearance of large number of vacuoles in cytoplasm and pyknotic nuclei in the liver of Channa punctatus and Anabas testudineus after intoxication of diazinon. Furthermore, Fernando et al [65] reported that, nuclear level impact of bispyribac-sodium on the fish, Poecilia reticulate was significantly higher number of damaged nuclei in liver tissue was noted in herbicide exposed fish Similar findings are compatible with the recorded histopathological lesions, which revealed a notable degeneration and necrosis of hepatocytes coincided with increasing in ASAT and ALAT activities [66][67][68][69] and confirming that, it may be attributed to liver injury [70][71].…”
Section: Discussionsupporting
confidence: 56%
“…Also,Rahmanet al [64] detected severe necrosis, appearance of large number of vacuoles in cytoplasm and pyknotic nuclei in the liver of Channa punctatus and Anabas testudineus after intoxication of diazinon. Furthermore, Fernando et al [65] reported that, nuclear level impact of bispyribac-sodium on the fish, Poecilia reticulate was significantly higher number of damaged nuclei in liver tissue was noted in herbicide exposed fish Similar findings are compatible with the recorded histopathological lesions, which revealed a notable degeneration and necrosis of hepatocytes coincided with increasing in ASAT and ALAT activities [66][67][68][69] and confirming that, it may be attributed to liver injury [70][71].…”
Section: Discussionsupporting
confidence: 56%